Estudio analítico de la metáfora y su traducción, ejemplificado en Memorial de Isla Negra de Pablo Neruda - Mohamed Saad, Saad (Dicenda. Estudios de lengua y literatura españolas, 2001)
The aim of this research is a linguistic study of metaphor and its translation. From the traditional point of view, the definition of the metaphor should concentrate upon: 1. The replacement of one element with the other. 2. The similarity between those two elements. Nevertheless, those two points are not necessarily essential to the formation of the metaphor. When analyzing the «metaphor», it is noticeable that there is a change in the internal order of the overall features representing the meaning of the word. In that way, some features are neutralized, meanwhile others become more relevant. Hence we analyze the metaphor here as a semantic neutralization process. The analysis of metaphor translation reveals the existence of three problematic issues: 1. The difference in connotative meaning in the two languages. 2. The originality of the metaphor in the two languages. 3. The difference in the structure of the metaphor in the two languages.